Strategi Jemput Bola Simpanan Wadi’ah Dalam Menjaga Loyalitas Nasabah di Btm Sang Surya Pamekasan - Arifin, Muhamad (Jurnal Indonesia Sosial Sains, 2022)
The fundamental problem with the implementation of performance appraisal in the old regulation, namely Government Regulation No. 46 of 2011, is the gap between employee performance and organizational performance. This study aims to analyze how the civil servant performance management system through Government Regulation No. 30 of 2019 can overcome the performance gap as occurred in Government Regulation No. 46 of 2011. The analysis is carried out using the concept of team flow and the Management by Objectives process in the Implementation of the Civil Servant Performance Management System. The research used a mixed method with concurrent mixed methods. The sample for quantitative analysis was taken as many as 106 employees of Regional Office VIII of the Civil Service Agency. The results of simple regression testing prove that team flow prerequisites affect and contribute positively to team flow characteristics with correlation and determination coefficients of 0.461 and 0.667, respectively. The first multiple regression test results show that one of the team flow prerequisite indicators, namely the level of security, has a significant effect and has the largest contribution to team flow characteristics with correlation and determination coefficients of 2.036 and 0.846, respectively. Based on the research results, this study recommends that in order for the gap not to be repeated, it is necessary to maximize the role of implementing Management by Objectives.